SAVREMENI ASPEKTI KULTURE INOVACIJA U OBLASTI PREHRAMBENE INDUSTRIJE KAO DELA POLJOPRIVREDNO-PREHRAMBENOG LANCA - Ivanov, Plamen (International Journal of Economic Practice and Policy, 2025)
Innovation is the driving force behind the development of enterprises and is vital to their survival. Starting a new business is often accompanied by the discovery of new market niches, the offering of innovative products, or the launch of new approaches to satisfy consumer preferences. Within a constantly changing environment, enterprises need to build an innovation culture that ensures the preservation of the focus on innovation. This report reviews the current concepts of innovation culture and the factors that determine it. Special attention is paid to the specifics of food industry enterprises. The food industry is representative of the low-tech sectors in terms of research and development costs. However, as a result of global crises (climate change, military conflicts, and interrupted supply chains), the importance of the sector and its potential to offer quality and healthy food is growing. The study analyses the interrelationship between innovation culture and the level of innovation activity in the field of food production as part of the agri-food chain. On this basis, a model of an innovation culture in the field of food production is proposed. The report represents case studies of the practice of enterprises in the sector. The aim is to test the relevance of the model and to identify the main factors that help enterprises develop innovation-oriented behavior, as well as the barriers that prevent it. In the end, guidelines for further improvements of the model and ideas for further areas of research are proposed.